Analisis Kritik tentang Kebijakan Standar Proses Pembelajaran Pendidikan Agama Islam - Khoirun Nisa' (LPPM IAI Hasanuddin Pare-Kediri, 2018)
The performance of teachers, especially teachers of Islamic Religious Education become the public spotlight, because they become figures in the formation of personality and noble character. The purpose of religious education according to Government Regulation No. 55 of 2007, on Religious and Religious Education, Chapter II article 2 paragraph 2 is for the development of the ability of learners in understanding, living, and practicing religious values ​​that harmonize their mastery in science and technology. To realize the purpose of education, the learning system should refer to the standard process. Process Standards is one of the national standards of education related to the implementation of learning in educational units to achieve the Graduate Competency Standards.